Editorial - Singh, M. P.; Sharma, B.; Armstrong, D.; Kumar, J. (Cellular and Molecular Biology, 2012)
Almost every fortnight we come across with one or other exciting developments in the frontline areas of biological sciences. Population explosion and consequent increased demand for food and energy are newer challenges. To address these challenges in right perspective to enhance the quality of our lives, environment and our planet has become priorities for life scientists. This requires rational exploitation of development in frontiers of biological sciences to solve multifaceted problems. Hence, a National Conference on "Frontiers in Biological Sciences” was planned and successfully organized by the Department of Biotechnology along with other science departments i.e. department of Environmental Science, Microbiology and Biochemistry during December 4-5, 2011 in the VBS Purvanchal University, Jaunpur-222001 (India) as a part of silver jubilee year celebrations of the University. A large number of committed researchers with diverse background from various parts of the world made the event very productive and successful. The presence of young researchers made it a special event for Jaunpur, a culturally rich city of northern India. The conference started with a key note address by Dr. Lalji Singh, Vice-Chancellor, Banaras Hindu University, Varanasi. Scientists/academicians and graduate students from many National and International Research Institutions, Universities and Colleges participated and presented more than one hundred research papers. There were five scientific sessions for oral presentations and two for poster presentations; one on each day. The subject areas included in this conference were genomics, proteomics, pharmaconomics, bioinformatics, biodegradation and bioremediation, bioprocess, enzyme and microbial technology, human food, health, agriculture and animal biotechnology, physiology, development biology, tissue culture and mushroom biotechnology. The success of the conference encouraged us to put the contributions from selected authors in the form of proceedings and to publish it as a special issue of a peer reviewed international scientific journal of repute, Cellular and Molecular Biology (CMB). In this special issue of Cellular and Molecular Biology we present some selected peer reviewed research articles presented and discussed in the conference. The first paper of this special issue by Singh and Singh focuses on a noble strategy to produce edible mushroom with enhanced yield and nutrition by degrading resistant agrowastes. The second paper by Pandey et al. reveals biodegradation potential of white rot fungus, Pleurotus towards sugarcane bagasse. The third paper by Ruhal et al. reports development of malate biosensor by immobilization of malate dehydrogenase on carbon nanotubes.The fourth paper of Vishwakarma et al. highlights the azo dye decolourization by immobilized extracellular enzymes of Pleurotus species. The fifth paper by Dash et al. describes the rpm gene as a genetic marker for human bacterial meningitis. The sixth paper of Bertoletti et al. discusses tyrosine kinases as cellular cofactors and potential therapeutic targets for HIV infection. The seventh paper by Sandalli et al. depicts the characterization of catalytic carboxylate triad in polE of Geobacillus kaustophilus HTA. The eighth paper by Kaushal et al. stresses on speB gene as a specific genetic marker for early detection of rheumatic heart disease in human. The ninth paper of Datta and Lal presents application of molecular markers for genetic discrimination of fusarium wilt pathogen. The tenth paper by Siddiqi et al. demonstrates the study on the distribution of different carnitine fractions in various tissues of bovine eye. The eleventh paper by Ong et al. describes preparation of biologically active single-chain variable antibody fragments that target the HIV-1 GP120 v3 loop. The twelfth paper by Singh et al. highlights the effects of UV-B radiation on moss and lichen of East Antarctica and the thirteenth paper of Singh et al. shows impact of UV-B radiation on growth rate and nitrogen metabolism of cyanobacterial strains. The forteenth paper of Datta and Lal illustrates the changes in the chickpea and pigeonpea in response to Fusarium wilt. The fifteenth paper by Sharma et al. describes the effect of carbofuran on some biochemical indices of human erythrocytes under in vitro condition. In the sixteenth paper Singh et al. discusses bioethics as a new frontier of biological science. Adedeji et al. focuses on structural and biochemical basis for the difference in the helicase activity of two different constructs of SARS-CoV helicase in the seventeenth paper. Singh et al. in eighteenth paper reveals association of 5,10-methylenetetrahydrofolate reductase C677T polymorphism in susceptibility to tropical chronic pancreatitis in North Indian population In the nineteenth paper Sharma et al. presents in vitro carbofuran induced micronucleus formation in human blood lymphocytes. Ram Naraian et al. reports occurrence of plasmid linked multiple drug resistance in bacterial isolates of tannery effluent in the twentieth paper. Pandey et al. highlights antifungal and antioxidative potential of derived of Cinnamomum tamala in twenty first paper. The twenty second paper of Mishra and Rizvi describes Quercetin modulates Na+/K+ ATPase and sodium hydrogen exchanger in type 2 diabetic erythrocytes. Kumar et al. in twenty third paper depicts assessment of stress in freshwater fish, Channa punctatus. In the twenty forth paper Srivastava et al. reports acetylcholinesterase from human erythrocytes membrane as a screen for evaluating the activity of some traditional plant extracts. Singh et al. in the twenty fifth paper shows extracellular xylanase production by Pleurotus species. The twenty sixth paper by Kumar et al. illustrates the antioxidant effect of root extracts of Solanum xanthocarpum. The twenty seventh paper of Shukla et al. discusses the bioinformatic study of inhibition of P. falciparum pfATP6 by Curcumin. The twenty eighth paper of Michailidis describes effect of translocation defective reverse transcriptase inhibitors on the activity of N348I, a connection subdomain drug resistant HIV-1 reverse transcriptase mutant. The twenty ninth paper by Parveen et al. reports NMR-based metabonomics study in rats. We extend our gratitude to Prof. Sunder Lal, Vice-Chancellor, VBS Purvanchal University, Jaunpur, India for his support and encouragement to organize this conference. Prof. Sunder Lal very beautifully depicted the importance of Biological Science and Mathematical Sciences in his presidential address of the Conference. He further elaborated how marriage of these two sciences can help bring the revolution and possible solution of the problems faced by the mankind. The valedictory address was given by Prof. B.S. Srivastava, ex-Chairman, School of Biotechnology, JNU, New Delhi & Emeritus Scientist, CDRI, Lucknow, who appreciated the quality of presentations and also the local hospitality. The financial assistance from University Grants Commission (UGC), New Delhi is acknowledged with gratitude. We are also thankful to all contributors to this theme issue of CMB. Finally, we affectionately thank the volunteers who silently but effectively made the conference a great success. We offer special thanks to these individuals. We hope that this theme publication will be of some use for academicians and scientists working in different and exciting areas of modern biological sciences.